Soil and vegetation carbon pools in two community forests of Palpa district, Nepal - Khanal, Y; Sharma, RP; Upadhyaya, CP (Banko Janakari, 2011)
Quantification of carbon in any vegetation and soil type is a basic step for evaluating the carbon sequestration potential of an ecosystem. For quantification, soil samples from varying depths (0–20, 20–40, 40–60, 60-80 and 80–100 cm) of each soil profile were collected for each sample plot laid out in Jarneldhara and Lipindevi Thulopakho Community Forests (CFs) of Palpa district. Individual trees in the sample plots of both CFs were measured. Biomass of standing trees, poles and saplings were estimated indirectly from diameter at breast height (dbh) and total height by using allometric relationships, while the biomass of grass, herb and litter were calculated directly from field measurements. Above-ground and below-ground (root) carbon pools in Jarneldhara CF were found to be 36.6 ± 3.4 t ha-1 and 10.5 ± 1.0 t ha-1 , respectively; while those on Lipindevi Thulopakho CF were 40.2 ± 4 and 11.4 ± 1.1 t ha-1, respectively. Soil organic carbon pool in Jarneldhara and Lipindevi Thulopakho CF were 121.4 ± 7.4 and 94.6 ± 4.4 t ha-1, respectively. This indicates that CFs have high potential to offset large portion of carbon emission through sequestration into both soil and vegetation, and act as a natural carbon sink. Key words: Carbon pool; community forest; soil organic carbon; vegetation carbon; biomass DOI: 10.3126/banko.v20i2.4800 Banko Janakari Vol.20(2) 2010 pp.34-40